Rebecca & Lucie in the case of the missing neighbor - Girard, Pascal (Drawn & Quarterly, 2021)
"Rebecca's got an eight-month-old baby and a mystery to investigate! Late one summer night as she's breastfeeding Lucie, she spots two men carrying something heavy into a white minivan. It's probably nothing serious, but when Rebecca hears that a home healthcare provider named Eduardo Morales disappeared from the neighborhood that very night, she puts her detective hat on and gets to work."--